Reference values of skin autofluorescence - Koetsier, M; Lutgers, H L; de Jonge, C; Links, T P; Smit, A J; Graaff, R (Diabetes technology & therapeutics, 2010)
Skin autofluorescence (AF) as measured with the AGE Reader (DiagnOptics Technologies, Groningen, The Netherlands) is a noninvasive prognostic marker in diabetes mellitus and other diseases with increased cardiovascular risk. This study provides reference values of healthy Caucasian control subjects as a function of age, tobacco smoking, and gender. The results of skin AF measured in 428 healthy Caucasian control subjects by the AGE Reader (n = 211) and its nonautomated but otherwise similar predecessor, the Autofluorescence Reader (n = 217), were analyzed. Linear regression analysis was performed to obtain reference values for skin AF as a function of age. Further analysis was performed on the effect of tobacco smoking (n = 96) and gender. Skin AF was described by a linear increase with age of approximately 0.023 arbitrary units (AU) per year for subject age up to 70 years. Tobacco smoking was associated with an absolute increase of skin AF by 0.16 AU (P < 0.01), without a significant further increase with age (P = 0.17). Gender had no influence on skin AF in nonsmokers. Among current smokers, female subjects had a 0.2 AU higher skin AF than male subjects (P = 0.02), with no further age-related increase. The present results provide reference values of skin AF for healthy Caucasian control subjects over a broad age range. A major contribution of age and some interaction of smoking and gender were observed, resulting in reference values of skin AF suitable for clinical settings and future studies.